2009
DOI: 10.1038/nrneurol.2009.160
|View full text |Cite
|
Sign up to set email alerts
|

Primary dystonia: molecules and mechanisms

Abstract: Primary dystonia is characterized by abnormal, involuntary twisting and turning movements that reflect impaired motor system function. The dystonic brain seems normal, in that it contains no overt lesions or evidence of neurodegeneration, but functional brain imaging has uncovered abnormalities involving the cortex, striatum and cerebellum, and diffusion tensor imaging suggests the presence of microstructural defects in white matter tracts of the cerebellothalamocortical circuit. Clinical electrophysiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(134 citation statements)
references
References 109 publications
2
120
0
2
Order By: Relevance
“…Primary dystonia is a childhood-onset neurological illness characterized by disabling abnormal involuntary movements without consistent brain lesions on routine structural brain imaging or at postmortem analysis (1). This disorder is associated with several genotypes (2).…”
mentioning
confidence: 99%
“…Primary dystonia is a childhood-onset neurological illness characterized by disabling abnormal involuntary movements without consistent brain lesions on routine structural brain imaging or at postmortem analysis (1). This disorder is associated with several genotypes (2).…”
mentioning
confidence: 99%
“…In humans, the dystonia-specific Torsin1A (TOR1A) mutation TOR1A DE302/303 (also known as TOR1A DGAG ; referred to as Torsin DE in this paper) at the DYT1 gene locus is linked to early-onset primary dystonia (Tanabe et al, 2009). Mouse models expressing TOR1A DE302/303 accumulate abnormal vesicular structures at the NE (Goodchild et al, 2005;Naismith et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the shortcomings of the current genetic models of dystonia, they have in some cases demonstrated that loss or mutation of a particular dystonia gene can alter the function of neurons and connectivity of brain regions [29,44,50,[60][61][62][63]. Whether or not these dysfunctions are compensatory or causal in nature remains to be established.…”
Section: Rodent Models Of Dystoniamentioning
confidence: 99%